Teladan Yesus Kristus Bagi Kepemimpinan Pembawa Damai Dalam Implementasi Resolusi Konflik di Kota Surakarta - Irawan Budi Lukmono (IAKN TORAJA, 2021)
Abstract: Surakarta is a city with various religions, ethnicities, and groups. This diversity can be a positive value, but it can also be a negative value when conflicts and violence arise. Conflicts and violence in Surakarta are caused by changes and social divisions, economic disparities, ethnicity, culture, beliefs, politics, and education degrees. Thus, a series of conflicts, violence, and intolerance occurs almost every year. The goal of this research is to find a peacemaker leadership model that implements conflict resolution in the city of Surakarta based on the example of Jesus Christ. This research uses a phenomenological paradigm. The approach used is a qualitative approach. How to collect data through observation, interviews, literature study. Data analysis or study uses several levels, namely: domain studies, taxonomic studies, component studies, and theme studies. The result of this study is a peacemaker leadership model in the implementation of conflict resolution in Surakarta based on the example of Jesus Christ. In conclusion, the peacemaker leadership model in implementing conflict resolution in Surakarta based on the example of Jesus Christ is a good model to practice. So, suggestions for peace leaders in Surakarta can put the proposed model into practice. Keywords: Conflict Resolution, Jesus Christ, Peacemaker Leadership, Abstrak: Surakarta merupakan kota dengan beragam agama, etnis, dan golongan. Keragaman ini bisa menjadi nilai positif, tetapi juga bisa menjadi nilai negatif saat konflik dan kekerasan muncul. Konflik dan kekerasan yang terjadi di Surakarta akibat perubahan dan pembelahan sosial, disparitas ekonomi, etnis, kultur, kepercayaan, politik, dan derajat pendidikan. Sehingga, rentetan konflik, kekerasan, dan intoleransi terjadi hampir tiap tahun. Tujuan riset ini untuk menemukan model kepemimpinan pembawa damai yang mengimplementasikan resolusi konflik di kota Surakarta berdasarkan teladan Yesus Kristus. Riset ini menggunakan paradigma fenomenologis. Ancangan yang dipakai yaitu ancangan kualitatif. Cara penghimpunan data melalui, observasi, interviu, studi pustaka. Analisis atau kajian data memakai beberapa tingkat yaitu: kajian domain, kajian taksonomi, kajian komponen, serta kajian tema. Hasil penelitian ini adalah model kepemimpinan pembawa damai dalam implementasi resolusi konflik di Surakarta berdasarkan teladan Yesus Kristus. Simpulannya model kepemimpinan pembawa damai dalam implementasi resolusi konflik di Surakarta berdasarkan teladan Yesus Kristus menjadi model yang tepat untuk dipraktikkan. Sehingga, saran bagi pemimpin perdamaian di Surakarta dapat mempraktikan usulan model tersebut. Kata-kata Kunci: Kepemimpinan Pembawa Damai, Resolusi Konflik, Yesus Kristus.